A systems approach to small group interaction - Tubbs, Stewart L., 1943- (New York : McGraw-Hill, 2012)
'The only book that integrates all important small group communication topics into a single comprehensive conceptual model, this text pioneered the systems approach for the group communication course. Each chapter begins with a brief preview, followed by a glossary of terms and a real life case study. The text material in each chapter is followed by several experiential exercises for skill development and two original readings'--
Includes bibliographical references and index.
Keywords: Teams in the workplace; Small groups; Organizational behavior